STUDENTS' PERCEPTION TOWARDS ENGLISH ONLINE LEARNING DURING THE COVID-19 PANDEMIC. - Veronika Veyzi Walangitan; Nurmin F. Samola; Rinny S. Rorimpandey (Program Studi Pendidikan Bahasa Inggris, 2022)
To find out students' perceptions of online English learning during the COVID-19 pandemic at SMAN 1 Kakas, is the purpose of this study. The research used is descriptive research with a quantitative approach. By using the survey method. Questionnaire is a tool to collect data. Thirty students of class XI semester 2 were randomly selected from class XI IPA, XI IPS, XI Language at SMAN 1 Kakas in the academic year 2021/2022 to be used as samples in this study. Research conducted by researchers found that students' perceptions of online English learning are students have positive perceptions, this is based on data analysis that has been carried out. At SMAN 1 Kakas the applications used to support the online learning process are the Google Class room, Zoom, Google Meet applications, but the most frequently used is the WhatsApp application. Students' perception of online English learning is that students have positive perceptions, this is based on data analysis that has been done. The percentages of some aspects show this. Perceptions with aspects of teaching materials 52%, perceptions with aspects of the atmosphere or learning environment 52%, and perceptions with aspects of student interaction 53.9%. On the category scale, 52% and 53.9% are included in the positive category. This study shows that students can adapt and adjust to all aspects of the online learning process, and online learning can also be a solution during a pandemic based on the findings that have been discussed